2011
DOI: 10.1182/blood-2010-12-325753
|View full text |Cite
|
Sign up to set email alerts
|

A human promyelocytic-like population is responsible for the immune suppression mediated by myeloid-derived suppressor cells

Abstract: We recently demonstrated that human BM cells can be treated in vitro with defined growth factors to induce the rapid generation of myeloid-derived suppressor cells (MDSCs), hereafter defined as BM-MDSCs. Indeed, combination of G-CSF ؉ GM-CSF led to the development of a heterogeneous mixture of immature myeloid cells ranging from myeloblasts to band cells that were able to suppress alloantigen-and mitogen-stimulated T lymphocytes. Here, we further investigate the mechanism of suppression and define the cell sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
278
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 308 publications
(302 citation statements)
references
References 28 publications
16
278
2
6
Order By: Relevance
“…2 ), which was recently described in bone marrow-derived MDSCs, is equivalent to MDSCs present in the blood of patients with stage IV breast cancer (45). These populations display the structure and markers of promyelocytes and are immunosuppressive.…”
Section: Cd16mentioning
confidence: 99%
“…2 ), which was recently described in bone marrow-derived MDSCs, is equivalent to MDSCs present in the blood of patients with stage IV breast cancer (45). These populations display the structure and markers of promyelocytes and are immunosuppressive.…”
Section: Cd16mentioning
confidence: 99%
“…CD34 + MDSC were first isolated from head and neck squamous cell carcinoma (HNSCC) patients due to their high abundance in this tumor (4). Clinical correlation studies in breast, colorectal, pancreatic, esophageal, and gastric cancer patients demonstrated that increased MDSC levels may be an important independent prognostic factor for survival (5,6). For lung cancer patients, MDSC level is negatively correlated with responsiveness to standard chemotherapy (7).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, MDSC subset levels in the peripheral blood of RCC patients vs healthy donors were compared and the results showed that total MDSC, as well as G-MDSC and I-MDSC, are elevated in patients, which is consistent with several other studies. 22,23 The levels of M-MDSC did not change significantly, probably due to its lowest subset proportion or its potential differentiation into G-MDSC or TAMs. 24,25 Total MDSC, G-MDSC and I-MDSC in the peripheral blood of RCC patients correlated with increasing tumor grade.…”
Section: Discussionmentioning
confidence: 99%